1989
DOI: 10.4049/jimmunol.143.3.877
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of early murine hemopoietic progenitor cell proliferation after in vivo locoregional administration of transforming growth factor-beta 1.

Abstract: Transforming growth factor-beta 1 (TGF beta 1) has been shown in vitro to be a potent negative regulator of growth and differentiation of early hemopoietic progenitor cells, but not of more mature progenitors. However, little information is yet available regarding similar effects in vivo. We have developed an approach whereby TGF beta 1 can be administered locoregionally to the bone marrow via direct injection into the femoral artery. Our studies show that intrafemoral administration of a single bolus dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…87,88 Early in vitro studies in both human and mouse suggested that TGF-β1 and 3 mediated antiproliferative effects on hematopoietic stem/progenitor populations. 89 However, a precise understanding of the role of TGF-β signaling in vivo has been difficult to obtain due to the complexity of the phenotypes exhibited by mice deficient in TGF-β signaling components. The majority of Tgf-β1 −/− mice die in utero at day E10.5 from multiple developmental defects, whereas the few that survive to adulthood develop a wasting disease due to an autoinflammatory condition.…”
Section: Tgf-β Familymentioning
confidence: 99%
See 1 more Smart Citation
“…87,88 Early in vitro studies in both human and mouse suggested that TGF-β1 and 3 mediated antiproliferative effects on hematopoietic stem/progenitor populations. 89 However, a precise understanding of the role of TGF-β signaling in vivo has been difficult to obtain due to the complexity of the phenotypes exhibited by mice deficient in TGF-β signaling components. The majority of Tgf-β1 −/− mice die in utero at day E10.5 from multiple developmental defects, whereas the few that survive to adulthood develop a wasting disease due to an autoinflammatory condition.…”
Section: Tgf-β Familymentioning
confidence: 99%
“…Early in vitro studies in both human and mouse suggested that TGF‐ β 1 and 3 mediated antiproliferative effects on hematopoietic stem/progenitor populations 89. However, a precise understanding of the role of TGF‐ β signaling in vivo has been difficult to obtain due to the complexity of the phenotypes exhibited by mice deficient in TGF‐ β signaling components.…”
Section: Extrinsic Signaling and The Bm Nichementioning
confidence: 99%